Porphyrin‐based bridged silsesquioxane nanoparticles for targeted two‐photon photodynamic therapy of zebrafish xenografted with human tumor - Dib, Soraya (Cancer Rep (Hoboken), 2019)
BACKGROUND: Bridged silsesquioxane nanoparticles (BSNs) recently described represent a new class of nanoparticles exhibiting versatile applications and particularly a strong potential for nanomedicine. AIMS: In this work, we describe the synthesis of BSNs from an octasilylated functional porphyrin precursor (PORBSNs) efficiently obtained through a click reaction. These innovative and very small‐sized nanoparticles were functionalized with PEG and mannose (PORBSNs‐mannose) in order to target breast tumors in vivo. METHODS AND RESULTS: The structure of these nanoparticles is constituted of porphyrins J aggregates that allow two‐photon spatiotemporal excitation of the nanoparticles. The therapeutic potential of such photoactivable nanoparticles was first studied in vitro, in human breast cancer cells in culture and then in vivo on zebrafish embryos bearing human tumors. These animal models were intravenously injected with 5 nL of a solution containing PORBSNs‐mannose. An hour and half after the injection of photoactivable and targeted nanoparticles, the tumor areas were excited for few seconds with a two‐photon beam induced focused laser. We observed strong tumor size decrease, with the involvement of apoptosis pathway activation. CONCLUSION: We demonstrated the high targeting, imaging, and therapeutic potential of PORBSNs‐mannose injected in the blood stream of zebrafish xenografted with human tumors.